Analisis Konsep Magrib Pada Tingkat Transaksi Penjualan Online di Kecamatan Kolaka - Siska Siska (Jurnal Ekonomi Bisnis Syariah, 2020)
The development of technology that forms the online system in socializing also affects the economic system that takes place online. The online system in muamalah activities should provide a positive side in facilitating activities that are able to bring the seller closer to the buyer without any restrictions on the seller's space. However, the positive side will raise doubts about the muamalah system that is in accordance with Islamic law. Which raises several questions in the formulation of the problem, namely; how is the online buying and selling transaction system?, what are the benefits that arise from buying and selling online?, and whether online buying and selling does not contain elements of maghrib?. From the research conducted, it shows that in selling online there are two types of payment transaction models, namely there are those who pay half the price of the goods as collateral and there are those who pay in full after the goods arrive. The benefits of buying and selling online are that it makes it easier for online sellers to market their goods and for buyers no longer need to go to the store to look for the items they need. In buying and selling online there are also those that are not in accordance with Islamic law, as in this study there is an element of gharar in it, namely the difference in the color of the goods (clothing) as much as 98% because of the lighting when photographing the item. However, the element of gharar can still be forgiven because the element is still relatively small and there is voluntary action from both parties, especially to the buyer.